Le Tabulae di Brigetio e di Durostorum. Una constitutio sui privilegi di milites e veterani: lo status quaestionis - Castagnino, Francesco (Cultura giuridica e diritto vivente, 2020)
[The Tabulae of Brigetio and Durostorum. A constitution on the privileges of milites and veterans: the status quaestionis]. My research focuses on the main issues derived from the study of the Tabulae of Brigetio and Durostorum, in particular: the grant of tax privileges to soldiers and the supposed reform on the practice of issuing the military diplomas. On the latter point, I propose a different theory: the constitution transcribed in these tables introduced a new practice concerning the regular concession of the tabulae honestae missionis.